HR Management in Education: A Study of Natur Islamic School, Bekasi City and SIT Fitrah Hanniah, Bekasi Regency - Ade Chairil Anwar; Moh. Idrus (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
This study aims to get an overview of the management model of corporate-based teacher HR management in private Islamic schools as a residue of globalization and decentralization of education developed by the urban Muslim middle class by taking subjects in Sekolah Natur Islam (SANI) and Sekolah Islam Terpadu Fitrah Hanniah (SIT FH). This research is a qualitative research with a phenomenological approach. The results of this study show that: a) conceptually-theoretically the curriculum and independent learning developed by SANI and SIT FH are in line with the national education system: b) the management of teacher human resources at SANI and SIT FH has standard operating procedures (POS) that are tailored to the objectives of school education: and c) the development of SANI education focuses on micro moral development such as school digitalization, strengthening literacy, and model schools. Meanwhile, SIT FH focuses on macro material development such as infrastructure development and institutional development. Thus, this study confirms that diversification of educational development strategies, both in moral and material aspects, is a complementary approach to improving the quality of education holistically.